Computer modelling of electrical power systems - Arrillaga, J. (Wiley, 2001)
Annotation Computer models can be used to simulate the changing states of electrical power systems. Such simulations enable the power engineer to study performance and predict disturbances. Focusing on the performance of the power system boosted by the FACTS. (Flexible Alternate Current Transmission Systems), this timely update of a highly successful text responds to recent developments in power electronics. Comprehensive coverage includes * The mathematical background, algorithms and the basic tools needed to study complex power systems, their interaction and likely response to different types of network pathologies or disturbances * The latest improvements in network modelling techniques * Power electronics equipment. Written by an internationally renowned author in the field, this text is a valuable reference resource for practising engineers responsible for power supply systems as well as electrical engineering postgraduates.
Keywords: Electric power systems -- Mathematical models.; Electric power systems -- Data processing.; Electric power systems -- Computer simulation.; elektronické knihy; electronic books